Answer:
![f^(-1)(x)=-(x-72)/(32)](https://img.qammunity.org/2021/formulas/mathematics/high-school/btv6bxxg3a92x5trd6sepe5e0kgz11ank8.png)
Explanation:
To find the inverse function, you want to switch x with y and y with x, then solve for y.
y=-32x+72 [switch x with y and y with x]
x=-32y+72 [subtract both sides by 72]
x-72=-32y [divide both sides by -32]
![y=-(x-72)/(32)](https://img.qammunity.org/2021/formulas/mathematics/high-school/jkojlx7o5s7ockxxicliyw10ni2xcpz9sv.png)
Now, we have found the inverse function.